Effectiveness of integrated prophylactic antibiotics prescription in patients undergoing radiofrequency and microwave ablation of liver tumors: a retrospective cohort study - Pang, Wen Xuan; Hung, Kai Chee; Chua, Nathalie Grace Sy; Chung, Shimin Jasmine; Leong, Sum (The Interventionalist Journal, 2024)
An institutionalised in-house antibiotic prophylaxis (AP) guideline was developed in May 2019 to standardize AP prescription. This retrospective cohort study evaluated the effectiveness and clinical outcomes of the newly launched AP guideline on patients undergoing radiofrequency (RFA) and microwave (MWA) ablation of the liver from November 2018 to March 2020. Patients without high risk of biliary tree contamination were recommended a single dose of 2g IV cefazolin (or 600mg IV clindamycin in cases of beta-lactam allergy). Univariate analysis was conducted to evaluate the clinical outcomes. The study included 87 patients who underwent 93 procedures consisting of 18 RFAs and 75 MWAs for liver tumours. Concordance with AP guidelines improved significantly (38.5% vs. 87.0%; p<0.001). There were no ablation-related infections and mortality within 30 days post-ablation, and post-procedural nausea and vomiting were significantly reduced (15.4% vs. 1.9%; p=0.020). No significant difference in post-procedural fever (7.7% vs. 5.6%; p-value=0.693), chest and/or abdominal pain (5.1% vs. 7.4%; p=1.000) were noted. The newly implemented in-house antibiotic prophylaxis guideline streamlined AP prescribing in patients undergoing RFA and MWA. Additional research is needed to determine the effects on infection and mortality in patients with high-risk factors such as bile duct stents, sphincterotomies, and biliary-enteric anastomoses.